The seal of an official or an official seal?: the use of court seals in old babylonian Susa and Haft Tepe - Graef, Katrien de (JAOS, 2018)
This is an in-depth study of two exceptional seals impressed on tablets from late Sukkalmah-early Kidinuid Susa and Haft Tepe. Both seals have exceptionally long inscriptions in Akkadian, mentioning Išme-karāb and Inšušinak, respectively, followed by penalty and curse clauses resembling those used in the economic and legal texts and royal charters of Sukkalmah Susa. Analysis of the inscriptions implies that both seals must have been official seals, used by legal bodies during appeals to the supreme court. The Išme-karāb sealing, which mentions the deities Išme-karāb, escort of the dead to the underworld, and Inšušinak, judge of the dead, evokes divine judgement. The Inšušinak seal has a more secular and “national” character, invoking in the curse formula four important Elamite rulers, including the illustrious šilhaha.